Europeanisation and Regionalisation - Damjan Lajh (Czech Journal of International Relations, 2005)
This article focuses on the Europeanisation of regional policy and politics in Slovenia. It argues that the Europeanisation of regional development is closely linked to regionalisation, particularly for Slovenia, where there are still no officially recognised regions. This article highlights the importance of establishing a competent network of actors and institutions to coordinate and manage the EU's structural policy, and of a regional structure compatible with the NUTS classifications. Early indicators in Slovenia show that Europeanisation and regionalisation promoted the emergence of a relatively stable institutionalised network for administering the EU's regional development programmes, and boosted cooperation among subnational actors, which was poor in Slovenia during the last decade. My analysis shows that we can see the employment of subnational actors in Slovenia, rather than their actual empowerment.